METHODOLOGY DEVELOPMENT FOR THE DETERMINATION OF GAMMA EMITTING RADIONUCLIDES IN MOSS-SOIL (IAEA-447) AND STATISTICAL EVALUATION OF THE PROFICIENCY TEST RESULTS SUBMITTED TO THE IAEA - Iqbal, S.; Wasim, M.; Arif, M.; Anwar, Y. (The Nucleus, 2011)
The gamma spectrometry laboratory, Chemistry Division, PINSTECH, participated in the world-wide proficiency test organized by the International Atomic Energy Agency (IAEA) for the determination of radionuclides in moss-soil (IAEA447). The analysis methodology involved five standards IAEA-RGU-1, IAEA-RGTh-1, 9803SO, 9903SO and 0003SO for the quantification of 228Ac, 214Bi, 137Cs, 40K, 212Pb, 214Pb and 234Th. Although, all of our results were declared acceptable by the IAEA performance evaluation criteria even then we suggest the use of z-score, sum of rescaled z-score and sum of square of z-score as useful indicators